Implementasi Metode User Centered Design (Ucd) Pada Pembangunan Sistem Penyediaan Obat Berbasis Android - Muhammad Rifai; Muhamad Akbar (Jurnal Pengembangan Sistem Informasi dan Informatika, 2020)
The rapid development of information technology has an impact on behavior. The system is linked together to facilitate the flow of information, through a variety of androids, users are growing, and are very familiar with this technology is open to providing developers to create an application. User Center Design (UCD) is a design that is used because it presents the best approach if it describes from the initial stages of an interactive process. Information about the provision of medicine is desired without the need to go to his place.